THE EFFECT OF DOMINO GAME LEARNING MEDIA ON STUDENT LEARNING ACHIEVEMENTS - Erlina Rufaidah; Anisa Martiah; Kodri (Kusuma Negara Business School, 2020)
This study aims to find out how the effect of domino game learning media on students learning achievement of class VIII at SMP N 1 Padang, West Sumatera. The methodology of the research which is used in this research is experimental research. The research population was 256 students. The sampling technique used in the research is cluster random sampling, so that the sample acquired was class VIII-E which consisted of 34 students. The techniques of data collection used are documentation and tests. The techniques of data analysis are normality test, homogeneity test, and hypothesis test. Based on the research finding, there is significant effect of using domino game learning media on students learning achievements of class VIII at SMP N 1 Padang, West Sumatera.